Perancangan Presensi Perkuliahan Berbasis Mobile Pada Universitas Dinamika Bangsa - Abdul Rahim (LPPM STIKOM Dinamika Bangsa, 2021)
Dinamika Bangsa University is one of the universities in the city of Jambi. The attendance process for student lecture meetings is currently still being done manually. This has an impact on the process of recapitulation of lecture attendance to be longer and makes it difficult for the parties involved in it. In this study, an analysis was carried out related to the presence process in the dynamic university of the nation, the results of the analysis were used to design applications. This research produces a mobile-based application that can be used by lecturers and students for lecture attendance.